The household of God : lectures on the nature of the Church - Newbigin, Lesslie (SCM Press Ltd, 1953)
"The related themes of households and families figure prominently in the New Testament. On occasions Jesus taught about marriage, divorce, and more general familial relations. Paul likewise preached about families, extended families, figurative families, and codes of conduct for those inhabiting the same household. Peter provided direction to the church regarding relations between husbands and wives and parents and children. James counseled church membership to treat one another as "brothers" and "sisters." Jesus, Peter, and Paul also taught about the important contributions single members and widows make in the kingdom, and such household complexities as mixed-faith marriages. Thus, the New Testament contains much counsel for household conduct, familial relationships, and belonging to "the household of God.""--